2014
DOI: 10.1371/journal.pgen.1004239
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Evolution Is Associated with Pervasive Positive Selection on Globally Expressed Genes

Abstract: Cancer is an evolutionary process in which cells acquire new transformative, proliferative and metastatic capabilities. A full understanding of cancer requires learning the dynamics of the cancer evolutionary process. We present here a large-scale analysis of the dynamics of this evolutionary process within tumors, with a focus on breast cancer. We show that the cancer evolutionary process differs greatly from organismal (germline) evolution. Organismal evolution is dominated by purifying selection (that remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
91
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(102 citation statements)
references
References 52 publications
8
91
2
1
Order By: Relevance
“…The non-Darwinian prediction is consistent with the high K a /K s ratios (nonsynonymous/synonymous SNVs per site) observed in 400 cancer genomes (29) and in The Cancer Genome Atlas (TCGA) data (35). The ratio is statistically indistinguishable from 1 in most studies (36), thus indicating ineffective selection against protein sequence changes in tumors. Cases of K a /K s ∼ 1 are rarely seen in nature; for example, K a /K s < 0.3 between humans and other primates (1).…”
Section: Discussionsupporting
confidence: 77%
“…The non-Darwinian prediction is consistent with the high K a /K s ratios (nonsynonymous/synonymous SNVs per site) observed in 400 cancer genomes (29) and in The Cancer Genome Atlas (TCGA) data (35). The ratio is statistically indistinguishable from 1 in most studies (36), thus indicating ineffective selection against protein sequence changes in tumors. Cases of K a /K s ∼ 1 are rarely seen in nature; for example, K a /K s < 0.3 between humans and other primates (1).…”
Section: Discussionsupporting
confidence: 77%
“…4b). Using this new method, we analysed data from The Cancer Genomic Atlas (TCGA) and successfully identified as many as 134 novel putative tumour suppressors under a false discovery rate of 0.1 (Supplementary Table 3), a finding reminiscent of a recent study 23 and challenging the view that the growth of the cancer gene list has reached a plateau 17 . It is conceivable that most of the newly identified tumour suppressors are minor cancer drivers, conferring small fitness advantages in primary tumours.…”
Section: Resultsmentioning
confidence: 99%
“…Analyses of large-scale cancer somatic mutation data have revealed that the effects of positive selection are much stronger on cancer cells than on germline cells [16,17]. Given that many of the positively selected genes in tumor development act as the driving force behind tumor initiation and development and are thus considered "driver genes", it is understandable that almost all previous studies have focused on positively selected genes in cancer genomes [3,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have used the ratio of nonsynonymous to synonymous substitution rates to identify genes that might be under strong positive selection both in organismal evolution and carcinogenesis [11,16,17,[23][24][25][26]. However, most of these studies applied conventional methods, which are usually based on simple nucleotide mutation/substitution models, e.g., the simplest equal-rate model assuming that every mutation or substitution pattern has the same probability [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation